USE OF FORENSIC SCIENCE IN VICTIM IDENTIFICATION: A LEGAL STUDY. (International Journal of Food and Nutritional Sciences, 2022)
The identification of the suspect who committed the crime is revealed by forensicscience. The evidence makes it abundantly apparent what kind of crime was committed. Theincident's timing gets clear from the circumstances in which crime gets committed. The crime sceneof the offence is established by the forensic evidence.